Establishing the context for a Master degree programme in Nursing at the National University of Lesotho - Ntombifikile G. Mtshali; Isabel Nyangu; Nthabiseng Molise; Lineo Tsekoa; Mamotsamai Ranneileng; Malihaelo C. Qhobela; Ntsoaki Ralejoana (Elsevier, 2019)
The National University of Lesotho Nursing Department, in implementing the first Master degree programme in Nursing, conducted a rapid needs assessment to understand the nursing education status in the country, establish the nature of the Master degree programme suitable to meet needs of the country and identify the core competencies expected from the graduates produced from the Master degree programme. A quantitative survey was administered to registered nurses and/or midwives who were selected conveniently and 93 returned completed questionnaires. Data were analysed using Microsoft Excel Software and the SPSS (v23). Permission was sought from the Nursing Directorate at the Ministry of Health (Lesotho), participants gave informed consent and ethical principles were adhered to throughout the project.Pre-service Nursing and Midwifery Programmes were perceived as adequately preparing graduates for the health care system in Lesotho. The Master degree programme was perceived as necessary to strengthen the Nursing and Midwifery workforce and, specialisations to be prioritised were in line with the country's health agenda and national health priorities. Clinical specialisation with an option of a minor in nursing education or clinical leadership was identified as necessary. A number of competency areas were identified to serve as a guiding framework in competency-based curriculum development.Establishing the context is key in developing continuing education programmes that are relevant and responsive to needs of the population and health care system. Continued stakeholder input is necessary to ensure that the programme developed produces specialist nurses that add value to the nurse-driven health care system in Lesotho. Keywords: Context of Master degree, Master in Nursing, National University of Lesotho, Nursing competencies, Nursing education, Nursing specialisation